Robust Macroscopic 3D Sponges of Manganese Oxide Molecular Sieves. Issue 64 (25th September 2017) - Liu, Zhenxin; Wu, Depeng; Guo, Xuehui; Fang, Shaoming; Wang, Lizhen; Xing, Yu; Suib, Steven L.
Abstract: Invited for the cover of this issue is Zhenxin Liu, Yu Xing and co‐workers at the Zhengzhou University of Light Industry and the University of Connecticut. The image depicts robust macroscopic 3D sponges composed of pure phase manganese oxide molecular sieve nanowires. Read the full text of the article at 10.1002/chem.201702787 . Abstract : "This study sheds new light on manipulating properties of such sponges" Read more about the story behind the cover in the Cover Profile and about the research itself on page 16213 ff. (DOI:10.1002/chem.201702787 ).